Mechanism and Efficacy of Etanercept in Treating Autoimmune-like Manifestations of Coronavirus Disease 2019 in elderly individuals - Lizhong Zhang; Hongyi Li; Lei Shi; Jie Geng; Haojun Zhang; Haoran Chen; Peng Zhao; Yang Xiao; Jinqi Lu; Zhilun Li; Hongbin Pu; Chuandong Hou; et al. (Immunobiology)
During the COVID-19 pandemic, extensive research focused on universal treatments, but few studies addressed treatment regimens for elderly patients. This study aimed to evaluate the effects of etanercept, a TNF inhibitor, in elderly individuals with COVID-19 through observational analysis of compassionate use cases. The results showed that after one month of etanercept treatment, clinical indicators such as C-reactive protein, D-dimer, and fibrinogen normalised, whereas the control group receiving conventional treatment did not fully recover. Single-cell sequencing was performed on seven patients treated with etanercept and two uninfected individuals. Based on our data and in conjunction with external data, a comprehensive characterization map involving 400,000 cells was created. Transcriptomic analysis revealed autoimmune-like manifestations in elderly patients, highlighting the importance of immunotherapy. Plasma cells, platelets, and B cells were the most treatment-sensitive cells. Analysis of five drug types, including antiviral, etanercept, glucocorticoids, tocilizumab, and others, showed that tocilizumab was associated with an increased thrombosis risk in elderly patients. Meanwhile, etanercept alleviated autoimmune-like manifestations by inhibiting platelet factor 4 and suppressing TNF-α. Molecular docking showed etanercept's strong affinity (−15.0 kcal/mol) for the spike protein of the SARS-CoV-2 Omicron variant, suggesting it may protect immune-compromised patients. Our findings support etanercept as a potential treatment for elderly COVID-19 patients with autoimmune-like manifestations.